Analisis Integrasi Sistem terhadap Kepuasan Member GarudaMiles - Sugiharti, Sulisfiyani Wahyu; Darasta, You She Melly Anne (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
Advances in information technology require companies to continuously improve service quality through effective system integration. GarudaMiles, Garuda Indonesia's frequent flyer program, has implemented various innovations in its digital service system to enhance user satisfaction. This study aims to analyze the effect of system integration on GarudaMiles member satisfaction. A quantitative method was used, with a survey of 50 active GarudaMiles members. Data were analyzed using multiple linear regression to examine the relationship between system integration variables (ease of access, transaction speed, and data synchronization) and user satisfaction.The results indicate that system integration has a positive and significant impact on member satisfaction. Transaction speed has the most dominant influence compared to other variables. These findings demonstrate that optimizing a well-integrated digital system can enhance user experience and loyalty. This study recommends that Garuda Indonesia continue to evaluate and develop its information technology to maintain and enhance the satisfaction of loyal GarudaMiles customers.